• :00Days
• :00Hours
• :00Mins
• 00Seconds
A new era for learning is coming soon Suggested languages for you:

Europe

Answers without the blur. Sign up and see all textbooks for free! Q27E

Expert-verified Found in: Page 442 ### Linear Algebra With Applications

Book edition 5th
Author(s) Otto Bretscher
Pages 442 pages
ISBN 9780321796974 # Solve the initial value problem in ${\mathbf{f}}{\mathbf{\text{'}\text{'}}}\left(t\right){\mathbf{+}}{\mathbf{9}}{\mathbf{f}}\left(t\right){\mathbf{=}}{\mathbf{0}}{\mathbf{;}}{\mathbf{f}}\left(0\right){\mathbf{=}}{\mathbf{0}}{\mathbf{,}}{\mathbf{f}}\left(\frac{\mathrm{\tau \tau }}{2}\right){\mathbf{=}}{\mathbf{1}}$

The solution is. $\mathrm{f}\left(\mathrm{t}\right)=‐\mathrm{sin}\left(3\mathrm{t}\right)$

See the step by step solution

## Step 1: Definition of characteristic polynomial

Consider the linear differential operator

$\mathrm{T}\left(\mathrm{f}\right)={\mathrm{f}}^{\left(\mathrm{n}\right)}+{\mathrm{a}}_{\mathrm{n}-1}{\mathrm{f}}^{\left(\mathrm{n}-1\right)}+...+{\mathrm{a}}_{1}\mathrm{f}\text{'}+{\mathrm{a}}_{0}\mathrm{f}.$.

The characteristic polynomial of T is defined as

${\mathrm{p}}_{\mathrm{T}}\left(\mathrm{\lambda }\right)={\mathrm{\lambda }}^{\mathrm{n}}+{\mathrm{a}}_{\mathrm{n}-1}\mathrm{\lambda }+...+{\mathrm{a}}_{1}\mathrm{\lambda }+{\mathrm{a}}_{0}$.

## Step 2: Determination of the solution

The characteristic polynomial of the operator as follows.

$\mathrm{T}\left(\mathrm{f}\right)=\mathrm{f}\text{'}\text{'}+9$

Then the characteristic polynomial is as follows.

${\mathrm{P}}_{\mathrm{T}}\left(\mathrm{\lambda }\right)={\mathrm{\lambda }}^{2}+9$

Solve the characteristic polynomial and find the roots as follows.

${\mathrm{\lambda }}^{2}+9=0\phantom{\rule{0ex}{0ex}}{\mathrm{\lambda }}^{2}=‐9\phantom{\rule{0ex}{0ex}}\mathrm{\lambda }=\sqrt{‐9}\phantom{\rule{0ex}{0ex}}\mathrm{\lambda }=±3\mathrm{i}$

Therefore, the roots of the characteristic polynomials are $3i$ and $‐3i$.

## Step 3: Explanation of the solution

Since, the roots of the characteristic equation are different complex numbers.

The exponential functions ${\mathrm{e}}^{3\mathrm{it}}$ and ${\mathrm{e}}^{-3\mathrm{it}}$ form a basis of the kernel of T .

Hence, they form a basis of the solution space of the homogenous differential equation is $\mathrm{T}\left(\mathrm{f}\right)=0$.

Thus, the general solution of the differential equation $\mathrm{f}\text{'}\text{'}\left(\mathrm{t}\right)+9\mathrm{f}\text{'}\left(\mathrm{t}\right)=0$ is $\mathrm{f}\left(\mathrm{t}\right)={\mathrm{c}}_{1}{\mathrm{e}}^{3\mathrm{it}}+{\mathrm{c}}_{2}{\mathrm{e}}^{-3\mathrm{it}}$ .

## Step 4: Explanation of the solution with initial value problem

Consider the general solution of the $\mathrm{f}\text{'}\text{'}\left(\mathrm{t}\right)+9\mathrm{f}\text{'}\left(\mathrm{t}\right)=0$ with the initial value problem $\mathrm{f}\left(0\right)=0,\mathrm{f}\left(\frac{\mathrm{\pi }}{2}\right)=1$ is as follows,

$\mathrm{f}\left(\mathrm{t}\right)={\mathrm{c}}_{1}{\mathrm{e}}^{3\mathrm{it}}+{\mathrm{c}}_{2}{\mathrm{e}}^{-3\mathrm{it}}\phantom{\rule{0ex}{0ex}}\mathrm{f}\left(\mathrm{t}\right)=0\left({\mathrm{e}}^{3\mathrm{it}}\right)+1\left({\mathrm{e}}^{-3\mathrm{it}}\right)\phantom{\rule{0ex}{0ex}}\mathrm{f}\left(\mathrm{t}\right)=0+{\mathrm{e}}^{-3\mathrm{it}}\phantom{\rule{0ex}{0ex}}\mathrm{f}\left(\mathrm{t}\right)={\mathrm{e}}^{-3\mathrm{it}}$

Simplify further,

$f\left(t\right)=-\mathrm{sin}\left(3t\right)$

Hence the solution is $f\left(t\right)=-\mathrm{sin}\left(3t\right)$. ### Want to see more solutions like these? 